Double-Expressor Appendiceal Burkitt’s Lymphoma: A Case Report and Literature Review - Dukmak, Osama N.; Abugharbieh, Hamzeh M. I.; Emar, Mohammad Farid; Khamayseh, Iman; M. Tos, Salem; Salhab, Rafiq (Case Reports in Hematology, 2022)
Background. Appendiceal lymphoma is a very rare entity accounting for 0.015% of all gastrointestinal lymphoma cases. Acute appendicitis is the most common presentation of primary appendix neoplasms. Burkitt’s lymphoma presenting as an acute appendicitis is a rare entity with around 21% of the cases presenting as a lower iliac fossa mass. Case Presentation. A 23-year-old male was admitted to the surgical ward as a case of acute appendicitis with localized tenderness in the right iliac fossa, positive rebound tenderness, a positive Rovsing’s sign, and ultrasound findings of suspected complicated appendicitis. Appendectomy was performed. Histopathological examination of the appendectomy specimen revealed a double-expressor non-Hodgkin diffuse large cell lymphoma with Burkitt’s-like morphology. He was sent for chemotherapy treatment. Conclusion. Only 34 cases of Burkitt’s lymphoma have been reported to present as acute appendicitis. Histological examination following appendectomy for an apparent appendicitis is essential. Furthermore, complete blood count and a computed tomography scan aid the diagnosis of lymphoma. Double-expressor lymphoma has been shown to have poor outcomes. Therefore, prompt and aggressive treatment is vital.